Successful Practices and Policies to Promote Regulatory Reform and Entrepreneurship at the Sub-national Level - García Villarreal, Jacobo Pastor (OECD Publishing, 2010)
This report is part of the OECD-Mexico initiative "Strengthening of Economic Competition and Regulatory Improvement for Competitiveness". It summarises the findings of several case studies on best practices to promote regulatory reform and entrepreneurship at the sub-national level. It has benefited from the participation of three Mexican states (Baja California, Jalisco, and Puebla), as well as of three provinces from other countries, British Columbia (Canada), Catalonia (Spain), and Piemonte (Italy). By including both, Mexican and international experiences, this report derives practical lessons for sub-national governments to improve their regulatory quality and create dynamic business environments
Keywords: Governance